DRUG UTILIZATION EVALUATION OF ANTIBIOTICS IN THE DEPARTMENT OF PAEDIATRICS IN COMPLIANCE WITH THE WHO PRESCRIBING INDICATORS - POTLAPALLY NIKHITHA SRI; MOHAMMAD YOUNUS MOHIUDDIN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study is to analyze the drug utilization pattern of antibiotics according to the World Health Organization (WHO) prescribing indicators at an outpatient department of pediatrics. Methods: This is a prospective observational study conducted in an outpatient department of pediatrics in a private hospital located in Telangana, India. Study data were obtained from patient prescriptions and direct interview of the caretaker/patient. Results: Data have been collected from 295 pediatric patients, out of which 177 were male, the highest number of patients was reported in the age group of 1–4 years. Most of the patients presented with lower respiratory tract infection, acute gastroenteritis, and fever. Most of the prescriptions included ceftriaxone, amoxicillin + clavulanic acid, and quinolones among antibiotics. Conclusion: Most of the prescriptions were in accordance with the essential list of medicine for children given by the WHO, but the number of drug-drug interactions in the prescriptions were significant, which can be simply prevented by following standard therapeutic guidelines and by establishing a role of clinical pharmacist in the hospitals.